(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Water scarcity is the main problem in boro season in Bangladesh which limits growth and development of crop plants especially in rice. The field experiment was carried out at the Soil Science Field Laboratory of Bangladesh Agricultural University. The experiment was laid out in a split plot design with three replications. BRRI dhan29 was used as a test crop. Treatments were the combination of water saving techniques and different nutrients of organic and inorganic approaches. There were four types of water management viz. I1: minimum irrigation, I2: normal irrigation, I3: continuous flooding and I4: alternate wetting and drying (AWD). On the other hand five fertilizers management approaches viz. F1: 100% recommended fertilizer dose (RFD) chemical fertilizers (NPKSZn), F2: 75% RFD chemical fertilizers (NPKSZn) + 5 t ha-1 cowdung, F3: 75% RFD chemical fertilizers (NPKSZn) + 5 t ha-1 cowdung slurry, F4: 75% RFD chemical fertilizers (NPKSZn) + 3 t ha-1 poultry manure and F5: 75% RFD chemical fertilizers (NPKSZn) + 3 t ha-1 poultry manure slurry were tested. The water management practices were placed in the main plot and fertilizer management practices were given in the sub plots. Results revealed that minimum irrigation caused significant reductions in growth and yield of BRRI dhan29. On the other hand, AWD technique did not reduce the growth and yield of BRRI dhan29 in comparison to continuous flooding. It was also revealed that plant height, panicle length, number of effective tillers per hill and grains per panicle were significantly increased in I3F3 (continuous flooding with 75% RFD chemical fertilizers + 5 t ha-1 cowdung slurry) treatment compared to other treatments. The highest grain and straw yields were obtained from I3F3 treatment. Nutrient uptake by BRRI dhan29 responded significantly in I3F3 treatment which was statistically similar to I3F4, I4F5, I2F5, I4F4 and I4F3 treatments. Finally it can be concluded that application of continuous flooding or AWD with 75% RFD chemical fertilizers + 5 t ha-1 cowdung slurry showed better performance than other treatments for maintaining better rice production. J Bangladesh Agril Univ 19(1): 37-43, 2021 https://doi.org/10.5455/JBAU.15594